ORGANIZATIONAL COMMITMENT AS THE BLACK BOX TO CONNECT THE ISLAMIC WORK ETHICS AND EMPLOYEES BEHAVIOR TOWARD ORGANIZATIONAL CHANGE - Wartini, Sri; Harjiyanti, Wahyu (Jurnal Dinamika Manajemen, 2014)
The objective of the study was to examine the direct and indirect influences of Islamic work ethics on employees behavior toward organization change with organizational commitment as mediation. The population of the study was Public Civil Servants of the general inspectors of finance ministry. The samples were taken by Solvin method. It was a purposive sampling with 87 respondents. The results of the study showed that there was a direct influence of Islamic work ethics on organizational commitment, there was not any direct influence of organizational commitment on employees behavior toward organizational change, there was an indirect influence of Islamic work ethics on employees behavior toward organization change with organizational commitment as the mediation. It is concluded that there were a direct and an indirect influences of Islamic work ethics on employees behavior toward organizational commitmen as the mediation.Â Tujuan penelitian ini untuk menguji pengaruh langsung dan tidak langsung etika kerja Islami pada perilaku karyawan terhadap perubahan organisasi dengan komitmen organisasional sebagai mediasi. Populasi dalam penelitian ini adalah karyawan Pegawai Negeri Sipil di Itjen Kementerian Keuangan RI sebanyak 87 responden, menggunakan metode Slovin dengan teknik Purposive Sampling. Berdasarkan hasil penelitian menunjukkan, bahwa terdapat pengaruh langsung etika kerja Islami pada komitmen organisasional, tidak terdapat pengaruh langsung komitmen organisasional pada perilaku karyawan terhadap perubahan organisasi, terdapat pengaruh langsung etika kerja Islami pada perilaku karyawan terhadap perubahan organisasi dan terdapat pengaruh etika kerja Islami pada perilaku karyawan terhadap perubahan organisasi dengan komitmen organisasional sebagai mediasi. Penelitian ini menyimpulkan, bahwa ada pengaruh langsung dan tidak langsung etika kerja Islami pada perilaku karyawan terhadap perubahan organisasi dengan komitmen organisasional sebagai mediasi.